Fatigue of Micro Molded Materials - Aluminum Bronze and Yttria Stabilized Zirconia - Kennerknecht, Tobias (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2014)
Custom built setups were developed to investigate micro samples during quasistatic and cyclic testing in tension, compression and bending. Micro molded CuAl10Ni5Fe4-samples showed similar fatigue behavior compared to macroscopic samples due to both the sample size and microstructure being scaled down with the manufacturing process. Results from cyclic three-point bending tests on micro molded 3Y-TZP suggested that a minimum crack extension is necessary to develop cyclically degradable shielding.